2022
DOI: 10.1002/anie.202204565
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Fluorosulfate Based Inhibitors That Covalently Target the SIRT5 Lysine Deacylase**

Abstract: The sirtuin enzymes are a family of lysine deacylases that regulate gene transcription and metabolism. Sirtuin 5 (SIRT5) hydrolyzes malonyl, succinyl, and glutaryl ϵ‐N‐carboxyacyllysine posttranslational modifications and has recently emerged as a vulnerability in certain cancers. However, chemical probes to illuminate its potential as a pharmacological target have been lacking. Here we report the harnessing of aryl fluorosulfate‐based electrophiles as an avenue to furnish covalent inhibitors that target SIRT5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…The same group recently developed additional derivatives by introducing aryl fluorosulfate groups in order to obtain SIRT5 covalent inhibitors [ 171 ]. Starting from compound 8d , different derivatives have been designed to enhance water solubility.…”
Section: Pharmacological Modulation Of Sirt5mentioning
confidence: 99%
See 2 more Smart Citations
“…The same group recently developed additional derivatives by introducing aryl fluorosulfate groups in order to obtain SIRT5 covalent inhibitors [ 171 ]. Starting from compound 8d , different derivatives have been designed to enhance water solubility.…”
Section: Pharmacological Modulation Of Sirt5mentioning
confidence: 99%
“…These compounds were assessed for their influence on SIRT5-mediated deglutarylation at different incubation times (0–24 h). The parent compound 8k did not exhibit great variation over time (IC 50 (0 h) = 0.074 μM, IC 50 (24 h) = 0.103 μM), while compounds 8k - o exhibited time-dependent inhibition with IC 50 values at 0 h over 200 µM, which decreased to 18–36 µM after 4 h and 4.6–6.1 µM after 24 h incubation (IC 50 ( 8l ) = 6.1 μM, IC 50 ( 8m ) = 5.0 μM, IC 50 ( 8n ) = 4.6 μM, IC 50 ( 8o ) = 4.9 μM) [ 171 ]. LC-MS analysis indicated that 8l – o form covalent conjugates with SIRT5 and the presence of NAD + was shown to increase the rate of covalent formation.…”
Section: Pharmacological Modulation Of Sirt5mentioning
confidence: 99%
See 1 more Smart Citation
“…After bio-panning using the warhead-introduced peptide library, cyclic peptidic TCIs against cysteine- and serine-proteases were obtained. Using another approach, Taki’s group introduced a latent-electrophilic aryl fluorosulfate (i.e., fosylate [ 72 ]; Ar-OSO 2 F) warhead [ 41 , 73 ] which is completely inert and activated only in a matchmaking (i.e., enzyme-like) microenvironment [ 38 , 39 , 46 ] created between the target protein and an appropriate peptide during the reactivity and affinity-based [ 74 ] co-selection process of the T7 phage display [ 51 ]. The fosylate warhead minimized the promiscuous reaction during the library’s construction/selection, and a TCI was obtained with only 2 rounds of bio-panning.…”
Section: Recent Hot Topics Of Biotcimentioning
confidence: 99%
“…This is beneficial as the off-rate of small-molecule binding is reduced, enhancing target engagement. The targetable scope of nucleophilic amino acids has moreover expanded beyond cysteine, to encompass serine, lysine, and arginine, providing greater control of anchoring sites on the protein and expanded possibilities for more diverse tool compounds that stabilize protein complexes. Covalent drug discovery has already shown significant success in targeting challenging proteins, , which makes the strategy promising to molecular glue tool compound development.…”
Section: Introductionmentioning
confidence: 99%